2021
DOI: 10.21467/ajgr.11.1.71-79
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Effects of Seed Oil of Moringa oleifera Lam. on Albino Mice Infected with Plasmodium berghei (NK65)

Abstract: The study assessed the histopathological effects of seed oil of Moringa oleifera on albino mice infected with Plasmodium berghei. This work included a good idea in the treatment of a causing agent of malaria with Moringa seed oil as bio-natural treatment. Thirty-five mice were divided equally and grouped into five. The mice were acclimatised for seven days and thereafter infected with 0.2 mL Plasmodium berghei (NK65) parasite. The parasites were allowed to establish in the mice for five days before commencemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These studies regarded the extracts obtained from this species as biologically safe since the evaluated animals did not present relevant behavioral or physiological changes during the acute and subacute toxicity experiments. However, despite the extracts being considered safe, a recent study by Abdulahi et al [44] reported that precautions should be taken when administering M. oleifera seed oil at a dose greater than 200 mg/kg, as this product may be mildly toxic.…”
Section: Toxicity Of Moringa Oleiferamentioning
confidence: 99%
See 1 more Smart Citation
“…These studies regarded the extracts obtained from this species as biologically safe since the evaluated animals did not present relevant behavioral or physiological changes during the acute and subacute toxicity experiments. However, despite the extracts being considered safe, a recent study by Abdulahi et al [44] reported that precautions should be taken when administering M. oleifera seed oil at a dose greater than 200 mg/kg, as this product may be mildly toxic.…”
Section: Toxicity Of Moringa Oleiferamentioning
confidence: 99%
“…Ethnobotanical and ethnopharmacological surveys carried out in African and Asian countries have reported the use of M. oleifera for the treatment of malaria in traditional communities [31][32][33][34][35][36][37][38]. These ethnomedicinal uses have been confirmed through in vivo and in vitro assays using different products obtained from the leaves and seeds of M. oleifera against several malaria-causing species of Plasmodium [39][40][41][42][43][44]. It is important to emphasize that the phytochemicals isolated from this species have not yet had their antimalarial activity evaluated in scientific research.…”
Section: Introductionmentioning
confidence: 99%